EVALUATION OF REVERSAL EFFECTS OF EUGENIA JAMBOLANA SEED EXTRACTS AGAINST HIGH-FRUCTOSE DIET-INDUCED INSULIN RESISTANCE IN ALBINO RATS - Bayya, M.h.r.k Gupatha; Adiga Mn, Sachidananda; Nayak Im, Nagendra; Deb Roy, Asitava; Kumar Ak, Sampath (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to evaluate the reversal effects of aqueous and ethanolic extracts of jamun seeds against high-fructose (HFr) diet-induced insulin resistance (IR) in albino rats. Methods: Thirty male albino rats were divided into five groups (n=6), and all the group rats except normal control were provided with HFr (60% w/v) to their drinking water daily for 42 days. Group 1 and 2 served as a normal and fructose control. Groups 3, 4, and 5 were supplemented with metformin (MET 500mg/kg p.o) and aqueous and ethanolic extracts of jamun seeds (Jamun seed aqueous extract [JSAE] and Jamun seed ethanolic extract [JSEE] 1000 mg/kg of each p.o), from day 28 to day 42, respectively. Physical (body weights, food, and water intake) and biochemical (glucose, insulin, and lipid) parameters were estimated, and Homeostasis model assessment (HOMA)-IR values were calculated. Results: HFr diet significantly (p<0.05) increased weight gain and water intake with decreased food intake in rats. HFr-fed rats exhibited a significant (p<0.05) increase in fasting glucose, insulin, and lipid levels along with increased HOMA-IR values and confirms the development of IR. Supplementation with MET, JSAE, and JSEE significantly (p<0.05) restored the physical parameters and reversed fasting glucose and lipid levels in comparison with HFr control. Whereas, only JSAE had significantly reversed the fasting insulin levels in comparison with HFr control. HOMA-IR values were significantly (p<0.05) decreased in both the extract groups of HFr-fed rats, and the results were comparable to MET. Conclusion: Our study concludes that both aqueous and ethanolic extracts of jamun exhibit a significant reversal effect against HFr diet-induced IR, due to insulin-sensitizing actions at the target tissues.